2017
DOI: 10.18632/oncotarget.14488
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of supervised classifiers for fecal microbiota-based prediction of colorectal cancer

Abstract: Predicting colorectal cancer (CRC) based on fecal microbiota presents a promising method for non-invasive screening of CRC, but the optimization of classification models remains an unaddressed question. The purpose of this study was to systematically evaluate the effectiveness of different supervised machine-learning models in predicting CRC in two independent eastern and western populations. The structures of intestinal microflora in feces in Chinese population (N = 141) were determined by 454 FLX pyrosequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 43 publications
0
60
0
1
Order By: Relevance
“…A striking example is our recent identification of the link between Fusobacterium nucleatum and the chemoresistance to CRC . We and others also showed that gut microbiota alone could predict CRC well, highlighting a potential clinical application of gut microbiota as a noninvasive screen strategy for early detection of CRC in population . Despite the enormous efforts and substantial progress, only minor improvements have been achieved in the clinical outcome of patients with CRC.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A striking example is our recent identification of the link between Fusobacterium nucleatum and the chemoresistance to CRC . We and others also showed that gut microbiota alone could predict CRC well, highlighting a potential clinical application of gut microbiota as a noninvasive screen strategy for early detection of CRC in population . Despite the enormous efforts and substantial progress, only minor improvements have been achieved in the clinical outcome of patients with CRC.…”
Section: Introductionmentioning
confidence: 84%
“…We previously reported that gut microbiome was able to noninvasively screen CRC by employing supervised machinelearning algorithms, particularly Bayes Net and Random Forest algorithm. 11 Similarly, we tried to study whether the altered gut micobiome could discriminate tumor-bearing mice from control mice, or more strikingly, distinguish Synbindin flox mice from Synbindin ΔIEC mice. As expected, microbiota composition distinguished tumor-bearing mice from tumor-free mice with the performance of 1 AUC even at the phylum level( Fig.…”
Section: Ablation Of Synbindin Does Not Prevent Dss-induced Inflammatmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer (CRC) is one of the leading cancers worldwide, and its incidence has increased by 22% from 2000 to 2013 in the United States. In China, the prevention and treatment of CRC remain to be highly challenging tasks, given the complicated risk factors such as genetic background, environment, microbiota and immune‐related disorders. In metastatic CRC, the outcomes related to surgery or adjuvant therapy remain poor .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, acceptably sensitive classification or characterization could also not be achieved by unsupervised approaches, such as clustering and PCoA, while application of a supervised technique like group-regularised logistic regression analysis did achieve high predictive accuracy. This example of supervised machine learning is particularly useful for pattern recognition in highly complex data sets, such as the gut microbiome (40,41). Obviously, as mucosal biopsies are not likely to be routinely harvested in the follow-up of IBD patients, faecal samples have substantial advantages as biomarkers of both disease treatment and activity.…”
Section: Discussionmentioning
confidence: 99%